2007
DOI: 10.1016/j.idc.2007.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Microbiologic Investigations for Head and Neck Infections

Abstract: A variety of methods, including direct examination of stained smears, antigen detection, routine and special cultures, and histopathologic evaluation are available for investigation of head and neck infections. Newer rapid molecular techniques with increased sensitivity and specificity are becoming available at many centers. Evaluation of specific causes in head and neck infections is complicated by the tendency for polymicrobial infections, difficulty in obtaining adequate specimens, and the presence of a div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 48 publications
0
6
0
1
Order By: Relevance
“…and Klebisiella pneumoniae , the latter being more common in diabetic patients. 26 Sennes found Streptococcus viridans in 41.5% of the cases, Staphylococcus aureus in 20.7% of them, and 3.8% with Haemophilus influenza . 14 In our study, Streptococcus pyogenes was the most frequently detected agent (23.3%), which can be explained by the higher incidence of peritonsillar infections.…”
Section: Discussionmentioning
confidence: 95%
“…and Klebisiella pneumoniae , the latter being more common in diabetic patients. 26 Sennes found Streptococcus viridans in 41.5% of the cases, Staphylococcus aureus in 20.7% of them, and 3.8% with Haemophilus influenza . 14 In our study, Streptococcus pyogenes was the most frequently detected agent (23.3%), which can be explained by the higher incidence of peritonsillar infections.…”
Section: Discussionmentioning
confidence: 95%
“…Molecular techniques, eg, sequence-based analysis, such as 16S rRNA, have been advocated for organisms that are poorly cultivable or for identification when traditional phenotypic methods have failed. 13…”
Section: Discussionmentioning
confidence: 99%
“…3 Molecular techniques, eg, sequence-based analysis, such as 16S rRNA, have been advocated for organisms that are poorly cultivable or for identification when traditional phenotypic methods have failed. 13 In the past studies, S pyogenes, S aureus, and anaerobes were emphasized as predominant organisms in DNIs. 14 Although anaerobic cultures were not performed in all cases, 1 study reported that gram-negative organisms have replaced hemolytic streptococcus as the dominant pathogen in deep neck abscesses.…”
Section: Bacteriamentioning
confidence: 99%
“…Authors published that the most frequent bacteria were Streptococcus viridiana, and Staphylococcus aureus. On the other hand, Roscoe et al 18 and Caccamese at al. 19 detected Streptococcus viridana, Streptococcus milleri, Prevotella spp, Peptostreptococcus spp and Klebsiella pneumoniae.…”
Section: Discussionmentioning
confidence: 95%